KEPEGAWAIAN DI KESULTANAN SIAK: GAMBARAN ARSIP GAJI ERA SULTAN SYARIF KASIM II: Array - Iik Idayanti; Hadira Latiar (Jurnal Kearsipan, 2020)
The salary archive used in this study is a digital archive owned by the Siak Regency Library and Archives Office. The archive is a legacy of Sultan Syarif Kasim II's government (1915-1945). There are 3000 archives available. At present, there are not many writings that reveal the contents of this historical value archive, especially those relating to staffing, whereas in this historical archive there is a description of the sultan's policies in the welfare of his people. The purpose of this research is to identify and provide archival description relating to employee salaries. The method applied in this study is qualitative with a descriptive approach. The results showed that of the 3000 digital archives, 280 of them contained salary information for 100 employees. The identified file illustrates 3 things, namely the monitoring of the Colonial Government which was shown in the use of two languages ​​in the archive, namely Malay and Dutch; The government sistem is centralized, because direct employment is responsible to the Sultan; The Sultan appreciates the ability and service of his employees, this is reflected in the difference in salary received by each employee based on his tenure.